COMIC STRIPS AND BOARD GAME AS A MEDIA IN LEARNING ORAL LANGUAGE SKILLS FOR STUDENTS - Puan Suri Mira Annisa; Rafika Dewi Nst (Jurnal Darma Agung, 2020)
This research aims to find out the improvement of the students’ oral language skills using comic strips and board game as an instructional media in terms of its physical feasibility, design, color, material, images and text by using role-playing. The subject was the 1 st grade students of the English department of Unimed, consisted of 30 students for the field trial. This research was use classroom action research by Kemmis and Taggart. It was accomplished in two cycles. Each cycles consisted of four steps: planning, action, observation and reflection. The first cycle consisted of one meeting including giving material and pretest. The second cycle consisted of one meeting, given material and post-test. Based on the students' assessment, it was showed that the mean of pre-test was 52 and the mean of post-test was 88. And the higher score was 92. From the data, it indicated that using Comic Strips and Board Game in learning Oral Language Skills was effective, and the data concluded that the students’ have the improvement in speaking. The results showed that comic strips and board game were very good and feasible to be used as a media to learn oral language skills.